Cooling interventions for the protection and recovery of exercise performance from exercise-induced heat stress - Duffield, R. (Thermoregulation and human performance. Physiological and biological aspects, 2008)
The aim of this chapter is to review the literature on the use of cooling interventions in the protection of and recovery of performance from exercise-induced heat stress. This chapter will deal primarily with the effects of pre-cooling on the improvement in exercise performance and the effects of post-exercise cooling on recovery. While pre-cooling has received much research attention, the mechanisms resulting in enhanced performance remain equivocal and moreover, pre-cooling has previously only been considered effective for endurance performance. More recent research describing the effects of pre-cooling on exercise performance and prevention of heat-related illness will be examined. This chapter will also deal with the suppression of exercise performance following heat stress and the use of cooling methods to improve the recovery of muscle function and subsequent exercise performance. Given the use of cold water immersion as a recovery practice of many athletes, a surprising lack of research has been conducted on the effects of cooling as a recovery tool from heat stress. As such, this chapter will discuss the use of cooling interventions on both the prevention of heat stress and recovery of performance from exercise-induced heat stress.